UPAYA PENGENDALIAN KOMPLIKASI DIABETES MELITUS DI RT 08 KELURAHAN 22 ILIR PALEMBANG - Anggriani Utama, Yofa; Sabrina Nainggolan, Sutrisari Sabrina (Universitas katolik Musi Charitas, 2021)
Lack of public knowledge about diabetes mellitus and how to control diabetes mellitus will lead to potential pathological risks including infection, ulceration and amputation. In addition, during the Covid-19 pandemic, diabetes mellitus is one of the comorbid factors for Covid-19 that can lead to death in diabetes mellitus patients. The purpose of this community service activity is to increase public knowledge about complications of diabetes mellitus. and improve the patient's ability to prevent complications of diabetes mellitus by doing diabetic foot exercises. The method of implementing this service is by providing online health education to Diabetes mellitus patients. This health education is carried out online using the Google Meet media. This activity was attended by 60 participants. Based on the results of the activity, it was found that knowledge before being given education was 45 people (75%) of diabetes mellitus patients had poor knowledge about diabetes mellitus education and diabetic foot exercises. After being given education, there was an increase in knowledge as many as 50 people (83%) of community service participants had good knowledge about diabetes mellitus education and diabetic foot exercises.